2015
DOI: 10.1155/2015/341430
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug Resistance in Relapse and Refractory Multiple Myeloma

Abstract: Multiple myeloma (MM) is a hematological malignancy that remains incurable because most patients eventually relapse or become refractory to current treatments. Although the treatments have improved, the major problem in MM is resistance to therapy. Clonal evolution of MM cells and bone marrow microenvironment changes contribute to drug resistance. Some mechanisms affect both MM cells and microenvironment, including the up- and downregulation of microRNAs and programmed death factor 1 (PD-1)/PD-L1 interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 233 publications
(223 reference statements)
0
52
0
Order By: Relevance
“…We considered that this differential susceptibility to HVJ-E might result from different expression of genes targeted by HVJ-E, which determine cell fate. Previous studies demonstrated that aberrant c-Myc expression is associated with myeloma cell survival and proliferation [2, 5]. Therefore, we focused on the regulation of c-Myc expression in HVJ-E-treated MM cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered that this differential susceptibility to HVJ-E might result from different expression of genes targeted by HVJ-E, which determine cell fate. Previous studies demonstrated that aberrant c-Myc expression is associated with myeloma cell survival and proliferation [2, 5]. Therefore, we focused on the regulation of c-Myc expression in HVJ-E-treated MM cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, one major limitation of the existing drugs is the eventual emergence of drug resistance for nearly all patients, regardless of the treatment regimen or the initial response to treatment [3]. It is well known that bone marrow microenvironment changes, such as cell adhesion and cytokine-related induction of the JAK/STAT and PI3K/AKT pathways, are responsible for resistance to conventional and novel therapies [4, 5]. Because MM is characterized by a high level of genomic instability and complex cytogenetic aberrations [6, 7], many of these alterations, which include chromosomal translocation, methylation, gene mutation, and microRNA (miRNA) abnormalities, can contribute to drug resistance [3, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the development of drug-resistance in some hematological tumors, for example in CML (An et al, 2010), and the lack of effective treatments in other ones (Martelli et al, 2012; Yang and Lin, 2015; Zinzani et al, 2015), addressed researchers to the study of new molecular targets and innovative therapeutic agents.…”
Section: Introdutionmentioning
confidence: 99%
“…In the pathogenesis of numerous malignancies the roles of NF‐κB pathway have been documented in many cases . The activity of this cascade in tumour cells leads to the generation of many factors . Inhibitor of nuclear factor kappa‐B kinase (IKKb) is a key molecule in the NF‐κB pathway and regulates pro‐inflammatory activity of this pathway through phosphorylation and proteasomal degradation of the NF‐κB inhibitor (I‐κB) .…”
Section: Introductionmentioning
confidence: 99%